Prediction of Employee Well-Being Through Organizational Justice in the Hospitality Work Environment - Friday Ogbu Edeh; Dayo Benedict Olanipekun; Muhamad Mundu Mustafa; Blessing Friday Edeh; Christine Ainebyoona; Desmond Oben Neji; Derrick Ssekajugo; Lilian Asinai; Aisha Najjuma; Kibuuka Muhammad (Asia Pacific Journal of Management and Education (APJME), 2025)
The issue of employee well-being has dominated discussion amongst scholars from interdisciplinary congregations quite apart from hospitality business practitioners. It was this debate that gave rise to this research. Therefore, this research aims to investigate the significant effect of organizational justice on employee well-being in the hospitality work environment based on a cross-sectional survey design. Twenty four-star hotels were selected using a simple random sampling technique. Data was collected with organizational justice and employee well-being validated instruments. Ethical principles regarding the participants were followed to avoid being harmed or coerced. After the data cleaning process, the valid data representing participants’ information was analyzed with frequency distribution while linear regression was employed to analyze the formulated research hypotheses. A statistical package for the social sciences was used to perform the analysis. After the analysis, it was found that organizational justice significantly predicted employee well-being positively. This study concludes that distributive, procedural, and interactional justice enhance employee well-being in the hospitality sector. The findings suggest that managers can reduce turnover by integrating organizational justice into daily decisions.